The Deployment of A Mobile Clinic in Response to The Flash Flood Disaster in Surantih, A Village in West Sumatra, Indonesia - Mahathir; Gusti Sumarsih; Fitra Yeni; Windy Freska; Indah Febriyana; Puti Mahagandhi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The flash floods and landslides that occurred in Surantih, Pesisir Selatan Regency caused various health problems. Post-disaster emergency response has been well coordinated through government hospitals and public health centers. However, the analysis of the Crisis Center of the Indonesian Ministry of Health and the Public Health Office of Pesisir Selatan District indicates a potential decline in health conditions, both physically and psychologically. The risk of post-disaster illness and psychological trauma needs to be prevented through the provision of preventive-oriented health services. Barriers to access to health services, especially for residents still living in disaster sites and refugees who are scattered due to infrastructure damage, exacerbate the situation. Therefore, it is necessary to provide a mobile clinic to overcome these obstacles and prevent a decline in physical and psychological health conditions. This activity aims to make a real contribution to post-disaster health management, and actively involve stakeholders in the establishment of mobile clinics. The implementation of the mobile clinic was carried out at four points that reached victims affected by the cold lava disaster. The number of health workers deployed was 8 specialist doctors 6 nurses 2 pharmacists and 4 psychologists. Mobile clinics provide services for post-disaster health problems and post-disaster chronic diseases. From the results of screening and health history taking, there were 90 disaster victims who had health problems such as skin diseases, chronic diseases, and post-disaster trauma problems. The implementation of mobile clinics provides solutions to obstructed access during disaster events, immediate handling of post-disaster physical problems and provides continuity of care for chronic diseases when post-disaster health services stop.